(untitled) (Docentes 2.0 Journal, 2022)
Despite having a defined planning, a radical turn is given as a result of COVID-19, a situation for which no one was prepared, and even less so, the education sector. Due to the above, this article aims to investigate the strategies and alternatives to be used so that the students of basic secondary and technical secondary education of an educational institution acquire habits, styles and self-learning models in the adequate use of technological tools, contributing to the academic improvement. The research will be carried out under the analytical method, positivist paradigm, quantitative approach, descriptive design, non-experimental type; with an approximate population of 212 students, it shows 84 and supported in three aspects: (a) Initial survey on technological equipment that is available, how to use them; (b) Time spent in use; (c) Application as support material. The data collection technique will be carried out through forms in Google Forms, about the proper use of digital devices applied in the teaching-learning process. The analysis will be done with percentages, using the Likert-type scale response frequency technique. Finally, it will be determined the need for training the population in the proper use of Information and Communication Technologies (ICT); At the same time, redesign area plans, changing traditional models that give importance to technological aids in school activities, regardless of whether there is a pandemic or not.